Device for the electromechanics strengthening of cylinder tribconnections - Волинський, Б.С.; Диха, М.О. (Problems of Tribology, 2014)
Conducted analysis of structural features of technological equipment for electromechanics treatment and the represented modified construction of device for strengthening of cylinder surfaces of details of machines.